Envolvimento do receptor de potencial transitório vanilóide 1 na díade dor-depressão induzida por reserpina em camundongos - Fischer, Susana Paula Moreira (2019)
Fibromyalgia is characterized mainly as chronic widespread pain and the patients can present comorbidities like depression. Although pain and depression cause a notable impact on patients’ quality of life, the underlying pathophysiology of this disease remain incompletely elucidated. The transient receptor potential vanilloid type 1 (TRPV1) is involved in the development of painful and depressive behaviours, while the α-spinasterol, a TRPV1 antagonist, presents antinociceptive and antidepressant effects. The current study investigated the involvement of the TRPV1 channel and the possible effects of α-spinasterol on the pain-depression dyad in a fibromyalgia-like model in mice. This model was induced with a subcutaneous (s.c.) injection of reserpine (1 mg/kg) once daily for three consecutive days in male Swiss mice. Reserpine administration depleted monoamines on spinal cord, thalamus and cerebral cortex, increased the mice immobility time on the forced swimming test, induced hypersensitivity to capsaicin, and caused mechanical allodynia. The reserpine-induced mechanical allodynia was inhibited by SB-366791 (1 mg/kg, p.o.), a selective TRPV1 antagonist [with a maximum inhibition (Imax) of 73.4±15.5%] or by the single or 3-day-repeated administration of α-spinasterol (0.3 mg/kg, p.o.) [with Imax of 72.8±17.8% and 78.9±32.9%, respectively]. Both SB-366791 and α-spinasterol (single or repeated administration) inhibited the increase of the reserpine-induced immobility time. The reserpine-induced mechanical allodynia and the thermal hyperalgesia were abolished by TRPV1-positive fibers desensitization induced by previous resiniferatoxin (RTX) administration. In summary, we suggest that TRPV1 channel may be involved in the pain/depression development and maintenance in a fibromyalgia-like model, and the TRPV1 antagonist α-spinasterol could be an interesting therapeutic agent to treat the pain-depression dyad in fibromyalgia’ patients.